Optimalisasi Strategi Manajemen Diri Program Care, Love and Be Healty Kidney (CLBK) dalam Meningkatkan Self-Efficacy Pasien Penyakit Ginjal Kronis Stadium V di RSUD Harapan dan Do’a Kota Bengkulu - Yatimah yatimah; Yayat Suryati; Asep Badrujamaludin (Malahayati Nursing Journal, 2026)
ABSTRACT Stage V chronic kidney disease (CKD) is a progressive condition that requires renal replacement therapy, such as hemodialysis. Patients often experience physical and psychosocial challenges that can lower their self-efficacy, which is their confidence in managing their disease. Therefore, effective self-management strategies are needed to improve self-efficacy. This study aims to test the effectiveness of the Care, Love, and Be Healthy Kidney (CLBK) program in improving the self-efficacy of CKD patients. This study aims to test the effectiveness of the Care, Love, and Be Healthy Kidney (CLBK) program in improving the self-efficacy of Stage V CKD patients. This study used a quasi-experimental approach with a pre-post-test design with a control group. The sample consisted of 34 Stage V CKD patients undergoing hemodialysis at Harapan and Do'a Regional Hospital in Bengkulu City. The CLBK program was implemented for one month, with eight sessions for the intervention group, while the control group received standard care. The instrument used was the Chronic Kidney Disease Self-Efficacy (CKD-SE) questionnaire. The average self-efficacy score before the intervention in the control group was 170.29 with a standard deviation of 19.61. The average self-efficacy score after the intervention in the control group was 170.88 with a standard deviation of 19.27. Statistical tests yielded a p-value of 0.018 (p 0.05). The average self-efficacy score before the CLBK self-management intervention in the intervention group was 178.18 with a standard deviation of 25.09, and the average self-efficacy score after the CLBK self-management intervention was 213.14 with a standard deviation of 17.68. Statistical tests yielded a p-value of 0.000 (p 0.05). Self-management of the care, love and be healthy kidney (CLBK) program can increase the self-efficacy of CKD patients and is more effective than the control group. Keywords: Hemodialysis, Self-Management Of CLBK, Self-Efficacy.  ABSTRAK Penyakit ginjal kronis (PGK) Stadium V merupakan kondisi progresif yang membutuhkan terapi pengganti ginjal, seperti hemodialisis. Pasien sering kali mengalami tantangan fisik dan psikososial yang dapat menurunkan self-efficacymereka, yaitu keyakinan diri untuk mengelola penyakit. Oleh karena itu, diperlukan strategi manajemen diri yang efektif untuk meningkatkan self-efficacy. Penelitian ini bertujuan untuk menguji efektivitas program Care, Love and Be Healty Kidney (CLBK) dalam meningkatkan self-efficacy pasien PGK.  Penelitian ini bertujuan untuk menguji efektivitas program Care, Love and Be Healty Kidney (CLBK) dalam meningkatkan self-efficacy pasien PGK Stadium V.Penelitian ini menggunakan pendekatan Quasi-eksperimen dengan desain pre-post-test with control grup. Sampel terdiri dari pasien PGK Stadium V yang menjalani hemodialisis di RSUD Harapan dan Do’a Kota Bengkulu sebanyak 34 orang pada masing-masing kelompok. Pelaksanaan CLBK dilakukan selama 1 bulan dengan 8 kali pertemuan pada kelompok intervensi dan kelompok kontrol diberikan perawatan standar. Instrumen yang digunakan adalah kuesioner Chronic Kidney Disease Self-Efficacy (CKD-SE). Rata-rata skor self efficacy sebelum intervensi pada kelompok kontrol adalah 170,29 dengan standar deviasi 19,61, Rata-rata skor self efficacy setelah intervensi pada kelompok kontrol adalah 170,88 dengan standar deviasi 19,27. Hasil uji statistik diperoleh nilai p = 0,018 (p 0,05). Rata-rata skor self efficacy sebelum intervensi manajemen diri CLBK pada kelompok intervensi adalah 178,18 dengan standar deviasi 25,09, kemudian rata-rata skor self efficacy setelah intervensi manajemen diri CLBK adalah 213,14 dengan standar deviasi 17,68. Hasil uji statistik diperoleh nilai p = 0,000 (p  0,05). Manajemen diri program care, love and be healthy kidney (CLBK) dapat meningkatkan self-efficacy pasien PGK dan lebih efektif dibandingkan dengan kelompok kontrol. Kata Kunci: Hemodialisa, Manajemen Diri CLBK, Self-Efficacy.